Microstructure-based numerical estimation of effective elastic properties of porous zirconium carbide - Pazhin, Albert A. (AIP Conference Proceedings)
In this work, elastic properties of porous zirconium carbide are numerically estimated. Zirconium carbide is widely used as part of metal-ceramic composites. The material in question, being prepared by the sintering, possesses a residual porosity and yields a decrease in effective elastic moduli and strength of material. When developing the multiscale mathematical model of the deformation and fracture processes of ceramic-based composites it is useful to determine the effective characteristics of matrix. The main goal of this work is to determine shear and bulk moduli of porous zirconium carbide matrix. The RVE model is based on experimental data obtained by SEM method. According to SEM patterns the residual porosity is approximately 5%. The numerical modeling of samples loading is carried out in the framework of twodimensional finite-difference continuum mechanics approach using plain strain formulation. The obtained results indicate the sufficient decrease in effective elastic moduli of ceramics compared to the initial values of ZrC matrix. Obtained estimations satisfactorily correlate with available literature data.